Evaluation of Good Manufacturing Practice (GMP), Standard Sanitation Operating Procedure (SSOP) for Traditional Chicken Slaughterhouses In Malang City - Afrila, Akhadiyah; Rosyidi, Djalal; Ihsan, Moch. Nur; Purwadi, Purwadi (Publikasi Indonesia, 2023)
Sanitation practices in the process of slaughtering chickens are very influential on the occurrence of contamination of microorganisms so traditional chicken slaughterhouses (RPA) must apply good production practice procedures or Good Manufacturing Practices (GMP) and sanitation procedures or Sanitation Standard Operating Procedures (SSOP) to produce chicken meat that meets microbiological requirements. This study aims to evaluate the implementation of GMP and SSOP and categorize it in Traditional RPA in Malang City. The evaluation was carried out at 75 RPA in 5 sub-districts in the city of Malang where the GMP and SSOP aspects referred to NKV 2005 and SNI 01-6160-1999 with the weighting of each aspect. The evaluation results show that traditional RPA in the city of Malang in terms of fulfilling GMP and SSOP aspects are categorized at level III to level V. In terms of fulfilling GMP aspects, they are categorized as level III (6.6%) and level IV (93.3%). The SSOP aspect fulfillment profile is categorized as level III (15%), level IV (50.6%), and level V (35%). The highest GMP aspects that are not fulfilled by traditional RPA are location and environmental aspects (91%) as well as raw material handling and processing aspects (88%). The highest SSOP aspects that were not fulfilled were the sanitation aspect (79%) and the personal hygiene aspect (71%). Based on the evaluation results of the critical parameter aspects (weighted 2) several recommendations are prepared in order to increase the fulfillment of GMP and SSOP in traditional RPA.